2010
DOI: 10.1007/s11266-010-9123-y
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Better Maps of Social Service Provision: Using the Holy Cross Dispute to Illustrate More Effective Mapping

Abstract: Third-sector organizations provide essential services, but not all types of organizations operate equally well given different intensities of public problems. This article argues for maps that would help social service funding bodies. Those maps would include three elements: (1) a measure of service demanded by a community, (2) data on the full range of organizations able to supply those services, and (3) a chart that identifies those organizations that provide services at different intensities of need. By pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For example, the U.S. Federal Government has classified nonprofits into “tax categories—in order to make them ‘fiscally legible’” (Scott, 1998, p. 68, as cited in Nickel and Eikenberry, 2016, p. 399). Academic projects focused on the Global North (Never, 2011; Roudebush & Brudney, 2012), Global South (Brass, 2012; Fruttero & Gauri, 2005), and comparative mapping across both (Salamon & Sokolowski, 2016) assert that nonprofits are not legitimate policy actors if they are not formally defined, making mapping essential to legitimization of the sector. Mainstream efforts to map civil society thus reproduce “a mode of knowledge inquiry that facilitates statecraft” (Nickel & Eikenberry, 2016, p. 398) and maps comprising “uniform governable units” (p. 394).…”
Section: Part II Critical Framework and Discussion On Mapping Civil S...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the U.S. Federal Government has classified nonprofits into “tax categories—in order to make them ‘fiscally legible’” (Scott, 1998, p. 68, as cited in Nickel and Eikenberry, 2016, p. 399). Academic projects focused on the Global North (Never, 2011; Roudebush & Brudney, 2012), Global South (Brass, 2012; Fruttero & Gauri, 2005), and comparative mapping across both (Salamon & Sokolowski, 2016) assert that nonprofits are not legitimate policy actors if they are not formally defined, making mapping essential to legitimization of the sector. Mainstream efforts to map civil society thus reproduce “a mode of knowledge inquiry that facilitates statecraft” (Nickel & Eikenberry, 2016, p. 398) and maps comprising “uniform governable units” (p. 394).…”
Section: Part II Critical Framework and Discussion On Mapping Civil S...mentioning
confidence: 99%
“…Mainstream approaches to civil society mapping involve collating standardized information on nonprofits, NGOs, and voluntary organizations and groups, and, often, making these data publicly available (Appe, 2013). The benefits ascribed to civil society mapping include enhancing our understanding of the size and scope of the sector (Grønbjerg, 1994; Lampkin et al, 2001), facilitating comparison of the sector across various contexts (Heinrich, 2005; Salamon & Anheier, 1998; Salamon & Sokolowski, 2016), improving economic and democratic efficiency through regulation and collaboration (Fioramonti & Kononykhina, 2015; Never, 2011; Salamon & Sokolowski, 2016), and legitimizing the role of civil society in burgeoning democracies (Appe, 2011, 2012, 2013).…”
Section: Part I Contextualizing Bases Of Knowledgementioning
confidence: 99%
“…In the context of mapping civil society, we see a standardization of information and, at times, these data are more regularly publicly available through information technologies and innovations like GRNDS. Many scholars have suggested that mapping can enhance the understanding of the size and scope of organized civil society, facilitate useful comparisons across contexts, and improve social coordination and efficiencies (e.g., Never, 2011;Roudebush & Brudney, 2012;Salamon & Associates, 2004). Perhaps the strongest assertion is that mapping civil society helps to legitimize the sector (Salamon & Sokolowski, 2016).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Seemingly disconnected from the rich literature in human geography, nonprofit scholars have also developed a literature on nonprofit location to develop maps of the sector (Never 2010;2011). Bielefeld, Murdoch, and Waddell (1997) explore the demographic composition of neighborhoods in the Dallas metropolitan area and the types of nonprofit organizations that operate in those geographies.…”
Section: The Geography Of Public Servicesmentioning
confidence: 99%